Improved Hierarchical Codebook-Based Channel Estimation for mmWave Massive MIMO Systems - Yoon, Sung-Geun; Lee, Seung Joon (IEEE wireless communications letters, 2022)
A novel approach is proposed to improve channel estimation accuracy in hierarchical codebook-based beam search for millimeter-wave (mmWave) massive multiple-input and multiple-output (MIMO) transmissions with channels that are accessible only through analog beamforming. Our approach is targeted at overcoming the resolution limit of directional angle estimation. In the proposed method, the data transmission beam is determined based on either two or three candidate codewords in the bottom layer and their beamforming gains. Design of the optimal beam is derived by exploiting the analytic structure of codewords in the bottom layer of the hierarchical codebook. Compared to conventional schemes used to increase the angle estimation resolution, the proposed scheme presents a higher achievable data rate in practical signal-to-noise ratio (SNR) ranges as well as superior channel estimation accuracy. This is verified through simulation results. The proposed method requires fewer codewords to be probed for beam training compared to the conventional methods, which reduces complexity.